High-Up: A Remote Reservoir of Microbial Extremophiles in Central Andean Wetlands - Albarracín, Virginia H.; Kurth, Daniel; Ordoñez, Omar F.; Belfiore, Carolina; Luccini, Eduardo; Salum, Graciela M.; Piacentini, Ruben D.; Farías, María E. (Frontiers in Microbiology, 2015)
The Central Andes region displays unexplored ecosystems of shallow lakes and salt flats at mean altitudes of 3,700 m. Being isolated and hostile, these so-called “High-Altitude Andean Lakes” (HAAL) are pristine and have been exposed to little human influence. HAAL proved to be a rich source of microbes showing interesting adaptations to life in extreme settings (poly-extremophiles) such as alkalinity, high concentrations of arsenic and dissolved salts, intense dryness, large daily ambient thermal amplitude, and extreme solar radiation levels. This work reviews HAAL microbiodiversity, taking into account different microbial niches, such as plankton, benthos, microbial mats and microbialites. The modern stromatolites and other microbialites discovered recently at HAAL are highlighted, as they provide unique modern -though quite imperfect- analogues of environments proxy for an earlier time in Earth’s history (volcanic setting and profuse hydrothermal activity, low atmospheric O2 pressure, thin ozone layer and high UV exposure). Likewise, we stress the importance of HAAL microbes as model poly-extremophiles in the study of the molecular mechanisms underlying their resistance ability against UV and toxic or deleterious chemicals using genome mining and functional genomics. In future research directions, it will be necessary to exploit the full potential of HAAL poly-extremophiles in terms of their biotechnological applications. Current projects heading this way have yielded detailed molecular information and functional proof on novel extremoenzymes: i.e. DNA repair enzymes and arsenic efflux pumps for which medical and bioremediation applications, respectively, are envisaged. But still, much effort is required to unravel novel functions for this and other molecules that dwell in a unique biological treasure despite its being hidden high up, in the remote Andes.